Social Cost of Motorcycle Accidents - A Case Study of the Bolgatanga Municipality - Kudebong, M. (University of Ghana, 2009)
Background Road traffic accidents are the leading cause of fatal and non-fatal injuries in Ghana. The purpose of this study is to estimate the social costs of motorcycle accidents in the Bolgatanga Municipality.. Method The study was a retrospective cross-sectional cost study. Data on direct, indirect and intangible costs were obtained from patients and their families using a structured questionnaire. The costs are calculated from the social perspective which includes out-of- pocket expenditure and productivity loss to patients and families, and cost to health facilities Results One hundred and sixty (I60) motor cycle accident victims were interviewed. The social cost of motor cycle accidents was found to be GH ¢1,630,979.60 per annum. Direct cost accounted for 64% of the total cost whilst indirect cost accounted 36% and on average twenty (20) days school absenteeism per student was established. It also imposes suffering such as pain, mostly waist pain, chronic headache and anxiety on victims and families. The working ability of victims reduced whereas a few were permanently disabled, reducing their quality of life.On average, motor cycle accident victims incurred direct costs of GH¢187, GH¢15, and GH¢128.15 respectively at the in-patient, out- patient and household level treatment , with time lost for normal activities averaging 32.5 days and 31.7days respectively for victims and caretakers respectively. The average cost of repair and replacement of damaged motor bikes were GH¢120.4 and GH¢1,106.21 respectively whilst the average item lost by victims was valued on average at GH¢186.99. The average cost of traditional funeral also averaged GH¢640.15. Conclusion Motor cycle accident costs the Bolgatanga municipality GH¢1,630,979.60 in social cost per annum. It also imposes pain, grief and suffering on victims and relations and in extreme situations where it involved permanent disability, it impacts negatively on health related quality of life of the victims. This calls for the allocation of appropriate resources and the enforcement of the existing legislation to nib this emerging epidemic in the bud.
Thesis (MPH)-University of Ghana